Effectiveness of hazard analysis and critical control point system based on microbial quality of poultry-based food and food contact surfaces - Subramaniam, Ramesh (2023)
Increased reliance is placed on the Hazard Analysis and Critical Control Point (HACCP) system to ensure poultry meat’s quality and microbiological safety in food service industries. However, epidemiological data revealed that many foodborne infections are attributed to the consumption of poultry meat, challenging the efficacy of the existing food safety system. This pronounced contrast necessitates a critical evaluation of the effectiveness of the HACCP framework in ensuring food safety. The study’s objective was to evaluate the effectiveness of HACCP applications through a 30-month assessment of their impact on the microbial quality focused on the presence of total plate count (TPC), coliform, Escherichia coli, Staphylococcus aureus, and Salmonella spp. in HACCP establishments. The analysis of 699 ready-to-market poultry meat samples from three companies revealed variable coliform and E. coli levels, indicating sporadic fecal contamination and episodic presence of S. aureus and Salmonella spp., which could be potential breaches in the HACCP system. The statistical analyses, Kruskal-Wallis and Mann-Whitney U tests, further confirmed these findings, showing significant differences (P<0.05) in TPC across companies. The expanded investigation into RTE foods and contact surfaces in 16 upscale dining and six private medical HACCP-certified establishments analyzed 377 RTE food and 825 contact surfaces, demonstrated variability in TPC and coliform levels. Medical establishments exhibited lower TPC and better microbial control than dining facilities, as shown by the Mann-Whitney U test (P<0.05). Nonetheless, hygiene issues were identified, with high non-compliance in TPC and coliform levels on contact surfaces and hands. Antibiotic susceptibility testing on isolates from poultry meat processing plants and food serving establishments revealed a concerning level of resistance among 23 Salmonella spp. to commonly used antibiotics such as ampicillin (100%), chloramphenicol (87%), and cephalosporins. Similarly, 30 S. aureus demonstrated high resistance rates to tetracycline (87.5%), chloramphenicol (81.2%), and penicillin (81.2%). The Multiple Antibiotic Resistance (MAR) index further highlighted the potential high risk of infection that may be difficult to treat with conventional antibiotics. This study reflects that the HACCP system failed to prevent the dissemination of resistant bacteria through the food chain. The study’s aim to investigate the adherence of isolated S. aureus to different types of surface material commonly used in food preparation environments (glass, GL; stainless steel, SS; and polyethylene, PE), with different surface conditions (with biofilm vs non-biofilm and rough vs smooth) as well as to evaluate the efficacy of chemical sanitizers (Quaternary Ammonium Compounds, QAC, and chlorine) in reducing bacterial adherence on these surfaces. Study shows that S. aureus’s adherence was high on rough surfaces and further increased with the presence of biofilm. Compared to PE, QACs demonstrated significantly better sanitization efficacy (P<0.05), on GL and SS smooth surfaces without biofilm. Choosing low-adherence surface materials in food facilities and determining optimal sanitization time for food-contact surfaces can be beneficial in ensuring food safety. The study conclusion is critical, highlighting the urgent need to enhance food safety compliance, particularly within HACCP-certified establishments. The current shortcomings of the HACCP system, especially in upscale dining venues, present a notable concern. This emphasizes the essential need for HACCP teams to apply HACCP principles effectively, especially in hazard identification, verification, and implementing corrective actions.